La détention provisoire et sa mesure - Tournier, Pierre (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1995)
Considering debates frequently raised in France concerning the situation of pre-trial detention, the author identifies some trends: the constant reference to statistics; lack of efforts to precise the meaning of indicators used in making a demonstration — in fact the same statistics can be used to demonstrate contradictory theses —, a largely spread habit to always speak of more : more use of pre-trial incarceration, more pre-trial detainees... Those practices, argue the author, lead to ignore important changes in trends and to avoid questioning the meaning of those. The limited interest in research using more sophisticated indicators — that could add usefully informations to the data published regularly by the prison administrations —, international comparisons between data not necessarily comparable, references to old statistics, all result in everyone continuing to attribute to France the European championship in terms of pre-trial detention, while the actual situation could be totally different. Considering all those elements, the author presents new bases to reanimate the debate on the question of the use of pre-trial detention.